2008
DOI: 10.1021/ja801383f
|View full text |Cite
|
Sign up to set email alerts
|

Coibamide A, a Potent Antiproliferative Cyclic Depsipeptide from the Panamanian Marine Cyanobacterium Leptolyngbya sp.

Abstract: Coibamide A (1) is a new, potent antiproliferative depsipeptide which was isolated from a marine Leptolyngbya cyanobacterium collected from the Coiba National Park, Panama. The planar structure of 1 was elucidated by a combination of NMR spectroscopy and mass spectrometry. Exhaustive 1D and 2D NMR spectroscopy included natural abundance 15 N and variable temperature experiments; mass spectrometry included TOF-ESI-MS n and FT-MS n experiments. Chemical degradation followed by chiral HPLC-and GC-MS analyses was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(187 citation statements)
references
References 9 publications
5
174
0
Order By: Relevance
“…9 Potent cytotoxic compounds from marine cyanobacteria the Panamanian marine cyanobacterium, Leptolyngbya sp. (Medina et al 2008 (Fig. 10), a cyclic depsipeptide, is a potent cytotoxic molecule isolated from a persistent strain of L. majuscula found at the western lagoon of Pulau Hantu, Singapore (Tripathi et al 2009).…”
Section: Bisebromoamidementioning
confidence: 99%
“…9 Potent cytotoxic compounds from marine cyanobacteria the Panamanian marine cyanobacterium, Leptolyngbya sp. (Medina et al 2008 (Fig. 10), a cyclic depsipeptide, is a potent cytotoxic molecule isolated from a persistent strain of L. majuscula found at the western lagoon of Pulau Hantu, Singapore (Tripathi et al 2009).…”
Section: Bisebromoamidementioning
confidence: 99%
“…A threonine residue allows not only closure of the macrocycle through an ester bond with the N,O-dimethyl-tyrosine residue, but also the presence of a tail of amino acids inserted onto its amino function. This feature is commonly found in numerous socalled "lariat-type" cyclic depsipeptides of marine origin, such as the families of lyngbyastatins (Kwan et al, 2009), the kahalalide F (which will be discussed below), hassallidin A (which contains a mannose branched on a threonine; Neuhof et al, 2005), and the remarkable almost fully N-methylated coibamide A (Medina et al, 2008), to mention but a few of the most outstanding compounds (Figure 13.14).…”
Section: Didemnins and Related Depsipeptides: How Perseverance Shouldmentioning
confidence: 96%
“…27.5) is a potent antiproliferative cyclic depsipeptide purified from the Panamanian marine cyanobacterial strain, Leptolyngbya sp. [62]. The discovery of this molecule stemmed from the International Cooperative Biodiversity Groups (ICBG) program, involving scientists from the US and Panama.…”
Section: Coibamide Amentioning
confidence: 99%
“…, and SNB-75 at2.8 nM, 7.4 nM, 7.4 nM, and 7.6 nM, respectively. Furthermore, "COMPARE-negative" analysis indicated that coibamide A might inhibit cancer cell proliferation via a novel mechanism [62]. Mode of action studies on coibamide A were recently conducted using human U87-MG and SF-295 glioblastoma cells and mouse embryonic fibroblasts (MEFs).…”
Section: Coibamide Amentioning
confidence: 99%